Enhance the therapeutic efficacy of human umbilical cord-derived mesenchymal stem cells in prevention of acute graft-versus-host disease through CRISPLD2 modulation - Qing Xu; Rui Wang; Ke Sui; Yuxi Xu; Ya Zhou; Yuxuan He; Ziyi Hu; Qi Wang; Xiaodong Xie; Xiaoqi Wang; Shijie Yang; Lingyu Zeng; et al. (Stem Cell Research & Therapy)
Abstract Background Acute graft-versus-host disease (aGVHD) remains a major life-threatening complication of allogeneic haematopoietic cell transplantation (allo-HSCT), often limiting the therapeutic efficacy of allo-HSCT. Recent studies have suggested that mesenchymal stem cells (MSCs) may be beneficial for the treatment of aGVHD. However, the therapeutic potential of MSCs is often negatively impacted by their heterogeneity. Methods To investigate MSCs heterogeneity, we conducted single-cell transcriptomic analysis of human umbilical cord-derived MSCs (HUC-MSCs) and identified key feature genes that distinguish MSCs subpopulations. The function of the newly discovered biomarker CRISPLD2 was also explored. We engineered human umbilical cord-derived MSCs (HUC-MSCs) to overexpress the CRISPLD2 gene using lentiviral vectors. The downstream regulatory effects of CRISPLD2 overexpression were assessed through bulk RNA sequencing. Additionally, we evaluated its impact on cellular senescence using Western blotting and β-galactosidase (SA-β-gal) staining. The immunoregulatory capability of HUC-MSCs was tested through coculture experiments with T cells and liver organoids in vitro. Mitochondrial function was analysed via flow cytometry and electron microscopy. The in vivo therapeutic effects of HUC-MSCs on aGVHD were evaluated using an aGVHD murine model. The graft-versus-leukaemia (GVL) effect was measured via the inoculation of luciferase-positive A20 cells, and tumour growth was monitored via bioluminescence imaging. Results Our findings indicated that the CRISPLD2 gene is heterogeneously expressed in HUC-MSCs subsets characterized by stemness and immunosuppressive properties. Transcriptomic analysis revealed that CRISPLD2 overexpression suppressed calcium ion binding and G protein-coupled receptor signalling. In vitro studies demonstrated a marked increase in IL-10 secretion, which enhanced T-cell suppression in CRISPLD2-modified HUC-MSCs. The in vivo results demonstrated that transfusion of CRISPLD2-overexpressing HUC-MSCs ameliorated aGVHD while maintaining GVL activity. Mechanistically, CRISPLD2 overexpression overcomes the mitochondrial damage mediated by extracellular ATP and LPS in HUC-MSCs by inhibiting P2Y11 receptor signalling, thereby preserving their stemness and IL-10-mediated immunosuppressive functions. Conclusions Our study revealed that CRISPLD2 is a novel marker for identifying HUC-MSCs subpopulation with enhanced immunosuppressive functions. CRISPLD2 overexpression enhances the immunosuppressive function of HUC-MSCs by inhibiting P2Y11 receptor signalling. Targeting CRISPLD2 is a promising strategy to improve the therapeutic efficacy of HUC-MSCs in aGVHD while maintaining GVL activity. Graphical abstract